Seasonal variation of blood pressure in maintenance hemodialysis - Castro, Manuel Carlos Martins de; Mion Jr., Décio; Marcondes, Marcello; Emil Sabbaga (São Paulo Medical Journal, 1998)
CONTEXT: Seasonal variation in arterial blood pressure has been reported in studies with hypertensive and normotensive subjects. However, the influence of seasonal change on blood pressure of hemodialysis patients has not been reported. OBJECTIVE: To investigate the seasonal variation of blood pressure in Brazil, a tropical country, in patients on hemodialysis. DESIGN: Prospective, cohort study. SETTING: Dialysis unit of a tertiary medical center (a teaching hospital of the University of São Paulo School of Medicine, São Paulo). PATIENTS: Sixteen patients with chronic renal failure undergoing hemodialysis. OUTCOMES: Blood pressure, body weight, and ambient temperature were evaluated during 6 hemodialysis sessions carried out on 13 days during the four seasons. RESULTS: The diastolic blood pressure was lower in summer than in fall and winter (95 ± 8 vs 107 ± 10 and 101 ± 10 mmHg, respectively; p < 0.05). The same was observed with mean blood pressure (116 ± 8 vs 130 ± 11 and 124 ± 9 mmHg, respectively; p < 0.01). On the other hand, the ambient temperature was higher in summer than in fall and winter (23.0 ± 1.6 vs 19.5 ± 3.0 and 15.8 ± 1.9 ºC, respectively; p < 0.01). CONCLUSIONS: We concluded that for patients with chronic renal failure the blood pressure has a seasonal variation with higher pressures in fall and winter than in summer. Thus, further studies are needed to elucidate the impact of this observation on the adjustment of antihypertensive treatment and on morbidity and mortality in maintenance dialysis patients.